The performance of singapore SMEs : A MODEL THAT INSPIRES MOROCCO: La performance des PME singapouriennes : un modèle qui inspire le MAROC - Lamia, SABOUR ALAOUI (African Scientific Journal, 2021)
Résumé La PME constitue l’une des solutions économiques des pays industrialisés d’une part, et d’autre part, un des grands espoirs de développement économique pour les pays en voie de développement. La PME est considérée comme un acteur principal de la sphère économique. C’est là que se crée et se renouvelle constamment le tissu industriel d’une région ou d’un pays. Les PME sont une source importante de créativité, de vitalité et d'emploi. L’entreprise a la possibilité d’opter pour un ensemble de changements dans ses systèmes de gestion pendant une période donnée. Ce processus de mise en compétitivité met l’action sur l’évolution du système de gestion de l’entreprise. Notre recherche repose sur une démarche comparative entre le Maroc et le Singapour, il s’agit d’une étude Benchmark afin de dégager les solutions prises par ses entreprises pour résoudre les différents problèmes liés à l’organisation de l’entreprise. Mots clés : PME ; Performance ; Singapour ; Maroc. Abstract The SME is one of the economic solutions of the industrialized countries on the one hand, and on the other hand, one of the great hopes of economic development for the developing countries. The SME is considered to be a major player in the economic sphere. It is here that the industrial fabric of a region or country is constantly created and renewed. SMEs are an important source of creativity, vitality and employment. The company has the option of opting for a set of changes in its management systems over a given period of time. This competitive process puts action on the evolution of the company’s management system. Our research is based on a comparative approach between Morocco and Singapore, it is a Benchmark study in order to identify the solutions taken by its companies to solve the various problems related to the organization of the company. Keywords : SME ; Performance ; Singapour ; Maroc